An efficient strategy for the expression of Jingzhaotoxin-III in Escherichia coli - Meng Yao; Jing Wang; Lei Wu; Lu Min; Wen-Ying Li; Ling-Yun Zhu; Er Meng; Dong-Yi Zhang (Biotechnology & Biotechnological Equipment, 2017)
Jingzhaotoxin-III (JZTX-III), a 36-residue peptide cardiotoxin containing three pairs of disulphide bonds, has been characterized from the venom of the Chinese tarantula Chilobrachys jingzhao. JZTX-III is a promising target for drug development and clinical application, due to its specific inhibitory effects on the human voltage-gated potassium channel subtype hKv2.1 and sodium channel subtype hNav1.5, which are mainly expressed in the cardiac myocytes. The most direct way to obtain JZTX-III is by extraction from the native venom of the tarantula jingzhao, but the amount is often insufficient to meet research and clinical demands. Therefore, there is need for an efficient expression system that can provide a larger quantity of JZTX-III. In this paper, we utilized a galactose auto-induction system to assist the Escherichia coli strain SHuffle T7 Express to express recombinant JZTX-III, followed by in situ purification on a Ni-nitrilotriacetic acid (Ni-NTA) column. Subsequent experiments were performed to demonstrate the advantages of the galactose auto-induction method and to optimize the incubation conditions. Under the optimal expression conditions, the product of the purified bioactive recombinant JZTX-III reached 12.1 mg/L. Furthermore, it is expected that this expression method can be widely applied to the heterologous expression of other disulphide-bond-rich peptides.